physicscatalyst.com logo




Integration Important Questions | Class 12 Maths




Multiple Choice Questions

Question 1
$\int e^{5ln x}\; dx$ equals to
(a) \( \frac {x^5}{5} + C \)
(b) \( \frac {x^6}{6} + C \)
(c) \( 5x^4 + C \)
(d) \( 6x^5 + C \)

Question 2
The integral of \( \frac{1}{x} \) is:
(a) \( \ln |x| + C \)
(b) \( e^x + C \)
(c) \( x \ln |x| + C \)
(d) \( \frac{1}{x^2} + C \)

Question 3
What is the integral of \( e^x \)?
(a) \( e^x + C \)
(b) \( xe^x + C \)
(c) \( e^{x^2} + C \)
(d) \( \ln |e^x| + C \)

Question 4
Find the integral of \( 3x^2 \).
(a) \( x^3 + C \)
(b) \( x^2 + C \)
(c) \( \frac{3}{2}x^3 + C \)
(d) \( x^3 + 3C \)

Question 5
The integral of \( \sec^2 x \) is:
(a) \( \tan x + C \)
(b) \( \cot x + C \)
(c) \( \sin x + C \)
(d) \( \cos x + C \)

Question 6
$\int_{-1}^{1} \frac {|x-2|}{x-2} \; dx $ equals to
(a) 1
(b) -1
(c) 2
(d) -2

Question 7
The integral of \( \frac{1}{\sqrt{1 - x^2}} \) is:
(a) \( \sin^{-1} x + C \)
(b) \( \cos^{-1} x + C \)
(c) \( \tan^{-1} x + C \)
(d) \( \cot^{-1} x + C \)

Question 8
Find the integral of \( \frac{1}{1 + x^2} \).
(a) \( \tan^{-1} x + C \)
(b) \( \cot^{-1} x + C \)
(c) \( \sin^{-1} x + C \)
(d) \( \ln |x| + C \)

Question 9
The integral of \( \frac{1}{\sqrt{x}} \) is:
(a) \( 2\sqrt{x} + C \)
(b) \( \frac{1}{2\sqrt{x}} + C \)
(c) \( \sqrt{x} + C \)
(d) \( \frac{1}{\sqrt{x}} + C \)

Question 10
What is the integral of \( \sin^2 x \)?
(a) \( \frac{1}{2}(x - \sin x \cos x) + C \)
(b) \( \frac{1}{4}(x - \sin 2x) + C \)
(c) \( \frac{x}{2} - \frac{\sin 2x}{4} + C \)
(d) \( \frac{x}{2} + \frac{\sin 2x}{4} + C \)

Question 11
The integral of \( 2^x \) is:
(a) \( \frac{2^x}{\ln 2} + C \)
(b) \( 2^{x+1} + C \)
(c) \( \ln |2^x| + C \)
(d) \( e^{2x} + C \)

Question 12
Find the integral of \( \ln x \).
(a) \( x \ln x - x + C \)
(b) \( \frac{\ln x}{x} + C \)
(c) \( x(\ln x - 1) + C \)
(d) \( \ln |x| + C \)

Question 13
The integral of \( \tan x \) is:
(a) \( -\ln |\cos x| + C \)
(b) \( \ln |\sin x| + C \)
(c) \( \sec x + C \)
(d) \( \cot x + C \)

Question 14
What is the integral of \( \frac{1}{\cos^2 x} \)?
(a) \( \tan x + C \)
(b) \( \sec x + C \)
(c) \( \sin x + C \)
(d) \( -\cot x + C \)

Question 15
$\int x^2 e^{x^3} \; dx$ equals to
(a) \( \frac{1}{3}e^{x^3} + C \)
(b) \( \frac{1}{3}e^{x^4} + C \)
(c) \( \frac{1}{2}e^{x^3} + C \)
(d) \( \frac{1}{2}e^{x^2} + C \)

Question 16
Find the integral of \( \cos^2 x \).
(a) \( \frac{1}{2}(x + \sin x \cos x) + C \)
(b) \( \frac{1}{4}(x + \sin 2x) + C \)
(c) \( \frac{x}{2} + \frac{\sin 2x}{4} + C \)
(d) \( \frac{x}{2} - \frac{\sin 2x}{4} + C \)

Question 17
$\int_{2}^{4} \frac {x}{x^2 + 4} \; dx$ is:
(a) \( log \frac {17}{5} \)
(b) \( \frac {1}{4} log \frac {17}{6} \)
(c) \( \frac {1}{6} log \frac {17}{2} \)
(d) \( \frac {1}{2} \)

Question 18
$\int_{0}^{\pi/4} \sin 2x \; dx$ is:
(a) 1
(b) -1
(c) 1/2
(d) -1/2

Question 19
The integral of \( \frac{1}{x(x+1)} \) is:
(a) \( \ln |x| - \ln |x+1| + C \)
(b) \( \ln |x+1| - \ln |x| + C \)
(c) \( \ln |x^2 + x| + C \)
(d) \( 2\ln |x| - \ln |x+1| + C \)

Question 20
Find the integral of \( \frac{x}{\sqrt{1 - x^2}} \).
(a) \( -\sqrt{1 - x^2} + C \)
(b) \( \sqrt{1 - x^2} + C \)
(c) \( -\frac{1}{\sqrt{1 - x^2}} + C \)
(d) \( \frac{1}{\sqrt{1 - x^2}} + C \)

Answer 1-20

1. (b)
$e^{5ln x} = e^ {ln x^5} =x^5$
So
$\int e^{5ln x}\; dx= \int x^5 \; dx= \frac {x^6}{6} + C $
2. (a) \( \ln |x| + C \)
3. (a) \( e^x + C \)
4. (c) \( \frac{3}{2}x^3 + C \)
Use the power rule for integration: \(\int x^n dx = \frac{x^{n+1}}{n+1} + C\)
5. (a) \( \tan x + C \)
6. (d) -2
$\int_{-1}^{1} \frac {|x-2|}{x-2} \; dx = \int_{-1}^{1} \frac {-(x-2)}{x-2} \; dx= \int_{-1}^{1} -1 \; dx=-2$
7. (a) \( \sin^{-1} x + C \)
8. (a) \( \tan^{-1} x + C \)
9. (a) \( 2\sqrt{x} + C \)
Use the power rule. \( \frac{1}{\sqrt{x}} = x^{-\frac{1}{2}} \), so the integral is \( \frac{x^{-\frac{1}{2}+1}}{-\frac{1}{2}+1} = 2\sqrt{x} \).
10. (c) \( \frac{x}{2} - \frac{\sin 2x}{4} + C \)
Use the half-angle identity: \( \sin^2 x = \frac{1}{2}(1 - \cos 2x) \). Integrating this gives \( \frac{1}{2}x - \frac{1}{4}\sin 2x \).
11. (a) \( \frac{2^x}{\ln 2} + C \)
The integral of \( a^x \) is \( \frac{a^x}{\ln a} \), so for \( 2^x \), it is \( \frac{2^x}{\ln 2} \).
12. (a) \( x \ln x - x + C \)
By integration by parts, \( \int \ln x \, dx = x \ln x - \int x \cdot \frac{1}{x} \, dx = x \ln x - x \).
13. (a) \( -\ln |\cos x| + C \)
14. (a) \( \tan x + C \)
15. (a)
Integration by substitution
$t=x^3$
$dt=3x^2 dx$
$x^2 dx= \frac {1}{3} dt$
$\int x^2 e^{x^3} \; dx= \frac {1}{3} \int e^{t} \; dt= \frac {1}{3} e^t + C= \frac {1}{3} e^{x^3} + C$

16. (c) \( \frac{x}{2} + \frac{\sin 2x}{4} + C \)
Use the half-angle identity: \( \cos^2 x = \frac{1}{2}(1 + \cos 2x) \).
Integrating this gives \( \frac{1}{2}x + \frac{1}{4}\sin 2x \).
17. (d)
Integration by substitution
$t=x^2 + 1$
$dt=2x dx$
$x dx= \frac {1}{2} dt$
$\int_{2}^{4} \frac {x}{x^2 + 1} \; dx= \frac {1}{2} \int_{5}^{17} \frac {1}{t} \; dt= [\frac {1}{2} ln |t| ]_{5}^{17}= \frac {1}{2} log \frac {17}{5}$

18. (c) 1/2
$\int_{0}^{\pi/4} \sin 2x \; dx= [-\frac {1}{2} cos 2x]_{0}^{\pi/4}=\frac {1}{2}$
19. (a) \( \ln |x| - \ln |x+1| + C \)
Use partial fractions: \( \frac{1}{x(x+1)} = \frac{A}{x} + \frac{B}{x+1} \). Solving for A and B gives \( A = 1 \) and \( B = -1 \). Integrating gives \( \ln |x| - \ln |x+1| \).
20. (a) \( -\sqrt{1 - x^2} + C \)
Use substitution: Let \( u = 1 - x^2 \). Then \( du = -2x dx \). The integral becomes \( -\frac{1}{2} \int \frac{du}{\sqrt{u}} \), which is \( -\sqrt{u} \) or \( -\sqrt{1 - x^2} \).


Question 21
$\int \sec^3 x \; dx$

Answer

Apply integration by parts:
\[ \int \sec^3 x \, dx = \int \sec x \cdot \sec^2 x \, dx = \sec x \tan x - \int \tan x \cdot \sec x \tan x \, dx \]
\[ = \sec x \tan x - \int \sec x \tan^2 x \, dx \]
Now, use the trigonometric identity \( \tan^2 x = \sec^2 x - 1 \):
\[ = \sec x \tan x - \int \sec x (\sec^2 x - 1) \, dx \]
\[ = \sec x \tan x - \int \sec^3 x \, dx + \int \sec x \, dx \]
Notice that \( \int \sec^3 x \, dx \) appears on both sides of the equation. Let's denote this integral as \( I \):
\[ I = \sec x \tan x - I + \int \sec x \, dx \]
Adding \( I \) to both sides gives:
\[ 2I = \sec x \tan x + \int \sec x \, dx \]
Now, \( \int \sec x \, dx \) is a standard integral, equal to \( \ln | \sec x + \tan x | + C \). So,
\[ 2I = \sec x \tan x + \ln | \sec x + \tan x | + C \]
Therefore
\[ I = \frac{1}{2} \sec x \tan x + \frac{1}{2} \ln | \sec x + \tan x | + C' \]


Question 22
$\int e^{2x} \sin(3x+1) \; dx$

Answer

To solve the integral \( \int e^{2x} \sin(3x+1) \, dx \), we can use integration by parts twice. Integration by parts is based on the formula:
\[ \int u \, dv = uv - \int v \, du \]
For this integral, we'll apply the method twice. Let's start with the first application:
(a).First Application:
- Choose \( u = \sin(3x+1) \) and \( dv = e^{2x} \, dx \).
- Then, \( du = 3\cos(3x+1) \, dx \) and \( v = \frac{1}{2}e^{2x} \).
Applying integration by parts:
\[ \int e^{2x} \sin(3x+1) \, dx = \frac{1}{2}e^{2x} \sin(3x+1) - \frac{3}{2} \int e^{2x} \cos(3x+1) \, dx \]
(b). Second Application:
- For the remaining integral, choose \( u = \cos(3x+1) \) and \( dv = e^{2x} \, dx \).
- Then, \( du = -3\sin(3x+1) \, dx \) and \( v = \frac{1}{2}e^{2x} \).

Applying integration by parts again:
\[ \int e^{2x} \cos(3x+1) \, dx = \frac{1}{2}e^{2x} \cos(3x+1) + \frac{3}{2} \int e^{2x} \sin(3x+1) \, dx \]
Now, substitute this back into our first equation:
\[ \int e^{2x} \sin(3x+1) \, dx = \frac{1}{2}e^{2x} \sin(3x+1) - \frac{3}{4}e^{2x} \cos(3x+1) - \frac{9}{4} \int e^{2x} \sin(3x+1) \, dx \]
Let \( I = \int e^{2x} \sin(3x+1) \, dx \). Then, we have:
\[ I = \frac{1}{2}e^{2x} \sin(3x+1) - \frac{3}{4}e^{2x} \cos(3x+1) - \frac{9}{4}I \]
\[ \frac{13}{4}I = \frac{1}{2}e^{2x} \sin(3x+1) - \frac{3}{4}e^{2x} \cos(3x+1) \]
\[ I = \frac{2}{13}e^{2x} \sin(3x+1) - \frac{3}{13}e^{2x} \cos(3x+1) + C \]


Question 23
$\int \frac {\sin(x-a)}{\sin(x+a)} \; dx$

Answer

$=\int \frac {\sin(x+a -2a)}{\sin(x+a)} \; dx$
$=\int \frac {\sin(x+a)\cos2a -\cos(x+a) \sin 2a}{\sin(x+a)} \; dx$
$=\int \cos2a - \frac {\cos(x+a) \sin 2a}{\sin(x+a)} \; dx$
put $\sin(x+a)=t$
$\cos (x+a) dx dt$
$=\int \cos2a \; dx - \sin 2a \int \frac {1}{t} \; dt$
$=x \cos2a - \sin 2a ln |\sin(x+a)| + C$


Question 24
Evaluate
$\int _{0}^{3/2} |x \sin \pi x| \; dx$

Answer

To integrate \( \int_{0}^{3/2} |x \sin \pi x| \, dx \), we need to consider the behavior of the function \( x \sin \pi x \) over the interval \([0, \frac{3}{2}]\) and where it changes sign, since the absolute value affects the integral.
Within the interval \([0, \frac{3}{2}]\), \( \sin \pi x \) is zero at \( x = 0 \) and \( x = 1 \), and changes sign at these points. Therefore, we need to split the integral at \( x = 1 \):

1. From \( x = 0 \) to \( x = 1 \), \( \sin \pi x \) is positive, so \( |x \sin \pi x| = x \sin \pi x \).
2. From \( x = 1 \) to \( x = \frac{3}{2} \), \( \sin \pi x \) is negative, so \( |x \sin \pi x| = -x \sin \pi x \).

Therefore we can write the integral as:
\[ \int_{0}^{3/2} |x \sin \pi x| \, dx = \int_{0}^{1} x \sin \pi x \, dx + \int_{1}^{3/2} -x \sin \pi x \, dx \]
Let's solve these integrals separately:
1.First Integral \( \int_{0}^{1} x \sin \pi x \, dx \):
Applying integration by parts:
\[ \int x \sin \pi x \, dx = -\frac{x}{\pi} \cos \pi x + \frac{1}{\pi} \int \cos \pi x \, dx \]
\[ = -\frac{x}{\pi} \cos \pi x + \frac{1}{\pi^2} \sin \pi x + C \]
Evaluate this from 0 to 1:
\[ \left[ -\frac{x}{\pi} \cos \pi x + \frac{1}{\pi^2} \sin \pi x \right]_{0}^{1} \]
\[ = \frac{1}{\pi} \]

2. Second Integral \( \int_{1}^{3/2} -x \sin \pi x \, dx \):
Again Applying integration by parts:
\[ \left[ -\frac{x}{\pi} \cos \pi x + \frac{1}{\pi^2} \sin \pi x \right]_{1}^{3/2} \]
\[ = \left( -\frac{3}{2\pi} \cos \frac{3\pi}{2} + \frac{1}{\pi^2} \sin \frac{3\pi}{2} \right) - \left( -\frac{1}{\pi} \cos \pi + \frac{1}{\pi^2} \sin \pi \right) \]
\[ = \left( -\frac{3}{2\pi} \cdot 0 - \frac{1}{\pi^2} \cdot (-1) \right) - \left( -\frac{1}{\pi} \right) \]
\[ = \frac{1}{\pi^2} + \frac{1}{\pi} \]

Adding these two results together gives the total integral:
\[ \int_{0}^{3/2} |x \sin \pi x| \, dx = +\frac{1}{\pi} + \left( \frac{1}{\pi^2} + \frac{1}{\pi} \right) \]
\[ = \frac {2}{\pi} + \frac{1}{\pi^2} \]


Question 25
Evaluate
$\int _{1}^{4} |x-1| + |x-2| + |x-4| \; dx$

Answer

Answer is 23/3


Question 26
Evalute the integral
$\int \frac {x^2 + x +1}{(x+1)^2 (x+2)} \; dx$

Answer

Let
$\frac {x^2 + x +1}{(x+1)^2 (x+2)} = \frac {A}{x+1} + \frac {B}{(x+1)^2} + \frac {C}{x+2}$
or
$x^2 + x +1= A(x+1)(x+2) + B(x+2) + C(x+1)^2$
At x=-1, we get
$B=1$
At x=-2, we get
C=3
At x=0, we get
A=-2
Therefore
$\frac {x^2 + x +1}{(x+1)^2 (x+2)} = \frac {-2}{x+1} + \frac {1}{(x+1)^2} + \frac {3}{x+2}$
So,
$\int \frac {x^2 + x +1}{(x+1)^2 (x+2)} \; dx= \int \frac {-2}{x+1} + \frac {1}{(x+1)^2} + \frac {3}{x+2} \; dx $
$= -2 log |x+1| - \frac {1}{x+1} + 3log |x+2| + C$


Question 27
Evaluate
$\int \frac {x}{(x^2+1) (x-2)} \; dx$

Answer

Let
$\frac {x}{(x^2+1) (x-2)} = \frac {Ax+B}{x^2 + 1} + \frac {C}{x-1}$
or
$x= (Ax+B)(x-1) + C(x^2 +1)$
Comparing coefficent and solving ,we get
A=-1/2, B=1/2 and C=1/2
Therefore
$\frac {x}{(x^2+1) (x-2)} = \frac {-1/2(x-1)}{x^2 + 1} + \frac {1/2}{x-1}$
So,
$\int \frac {x}{(x^2+1) (x-2)} \; dx$
$=\int \frac {-1/2(x-1)}{x^2 + 1} + \frac {1/2}{x-1} \; dx $
$=\frac {1}{2} \int \frac {-x}{x^2 + 1} + \frac {1}{x^2 + 1} + \frac {1}{x-1} \; dx$
$= \frac {1}{2}[ \frac {-1}{2} log |x^2 + 1| + \tan^{-1} x + log |x-1| ] +C$


Question 28
(a) Integrate \( \frac{2x + 3}{(x - 1)(x + 2)} \) dx
(b) Integrate \( \frac{1}{x^2 - 1} \) dx
(c) Integrate \( \frac{1}{(x + 1)(x^2 + 4)} \) dx

Answer

(a)
Let
$\frac{2x + 3}{(x - 1)(x + 2)} = \frac {A}{x-1} + \frac {B}{(x+2)}$
$2x+3 = A(x+2) + B(x-1)$
or A= 5/3
B=1/3
So,
$\frac{2x + 3}{(x - 1)(x + 2)} =\frac {1}{3}[ \frac {5}{x-1} + \frac {1}{(x+2)}]$
Therefore
$\int \frac{2x + 3}{(x - 1)(x + 2)} \; dx= \frac {1}{3} \int [ \frac {5}{x-1} + \frac {1}{(x+2)}] \; dx$
$=\frac {1}{3} [ 5 \ln |x-1| + \ln |x+2| ] + C$


Question 29
Evaluate
$\int _{0}^{\pi/2} \frac {x\sin(x) \cos(x)}{\sin^4(x) + \cos^4(x)} \; dx$

Answer

Let $I =\int _{0}^{\pi/2} \frac {x\sin(x) \cos(x)}{\sin^4(x) + \cos^4(x)} \; dx$ -(1)
Using
$\int _{0}^{a} f(x) dx = \int _{0}^{a} f(a-x) dx $, we get
$I= \int _{0}^{\pi/2} \frac {(\frac {\pi}{2} -x) \sin (\frac {\pi}{2} -x) \cos(\frac {\pi}{2} -x)}{\sin^4 (\frac {\pi}{2} -x) + \cos^4 (\frac {\pi}{2} -x)} \; dx$
$I= \int _{0}^{\pi/2} \frac {(\frac {\pi}{2} -x) \sin (x) \cos(x)}{\sin^4 (x) + \cos^4 x)} \; dx$ -(2)
Adding (1) and (2)
$2I=\frac {\pi}{2} \int _{0}^{\pi/2} \frac {\sin(x) \cos(x)}{\sin^4(x) + \cos^4(x)} \; dx$
Dividing numerator and denominator by $\cos^4 x$, we get
$2I=\frac {\pi}{2} \int _{0}^{\pi/2} \frac {\tan (x) \sec^2(x)}{1+ \tan^4 (x)} \; dx$
Put $\tan^2 x= t$, then $2\tan (x) \sec^2(x) dx =dt$
Therefore
$I = \frac {\pi}{8} \int _{0}^{\infty} \frac {1}{1+t^2} \; dt $
$I= \frac {\pi}{8} [ tan^{-1} t] _{0}^{\infty}= \frac {\pi^2}{16}$



Also Read




Go back to Class 12 Main Page using below links
Class 12 Maths Class 12 Physics Class 12 Chemistry Class 12 Biology


Latest Updates
Synthetic Fibres and Plastics Class 8 Practice questions

Class 8 science chapter 5 extra questions and Answers

Mass Calculator

3 Fraction calculator

Garbage in Garbage out Extra Questions7